2023
DOI: 10.1007/s11218-023-09782-2
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perception of aggressive student behavior through the lens of chronic worry and resignation, and its association with psychophysiological stress: An observational study

Abstract: Aggressive student behavior is considered a leading risk factor for teacher stress. However, teachers' coping styles may affect how they perceive and respond to aggressive student behavior. This study tests whether teachers' perceptions of aggressive student behavior mainly mirror objectively observed aggression in presence of the teacher (as coded by external observers) or whether teachers' perception of aggressive student behavior primarily reflects teachers' avoidant coping styles, such as chronic worry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…It provides insights into individual characteristics that may influence instructional practices and classroom dynamics. The high internal consistency further supports the questionnaire’s reliability as a measurement tool [ 39 , 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 74%
“…It provides insights into individual characteristics that may influence instructional practices and classroom dynamics. The high internal consistency further supports the questionnaire’s reliability as a measurement tool [ 39 , 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 74%
“…However, there is evidence that high chronic psychological stress affects teacher perceptions. For example, a study from the same project showed that chronically worried teachers systematically overestimated the extent of student aggression in their class [56].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, personality traits such as neuroticism and dysfunctional coping styles are associated with increased perceptions of aggressive student behavior [53][54][55]. Specifically, teachers with high resignation tendencies and chronic worry seem to systematically overestimate aggressive student behavior in their classrooms [56].…”
Section: Transactional Factorsmentioning
confidence: 99%
“…Stress stemming from student-related factors pertains to the tension triggered by challenges in students' academic performance and behavioral issues. For instance, teachers' perception of student aggression has been linked to teachers' reports of exhaustion (Wettstein et al, 2023). Self-development stress refers to the strain experienced by teachers due to factors such as curriculum reform and the educational evaluation system, particularly evident in the Chinese context (Peng, 2021).…”
Section: The Relationship Between Job Stress and Burnoutmentioning
confidence: 99%